Project DARE Teaching Kids To Say "No" to Drugs and Alcohol - DeJong, William; Department of Justice, Washington, DC. National Inst. of Justice ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
A joint project of the Los Angeles Police Department and the Los Angeles Unified School District, Project DARE (Drug Abuse Resistance Education) is designed to equip elementary and junior high school children with the skills for resisting peer pressure to experiment with drugs and alcohol. The goal is to teach students how to say "no." A growing consensus among experts in education and medicine holds that substance abuse prevention must begin early, well before children have been led by their peers to experiment with drugs and alcohol. Most important, Project DARE introduces this training just at the time when the peer pressure begins. DARE's instructors are Los Angeles police officers on full-time duty with the project. Assigned to five schools per semester, the officers visit classrooms once a week to present an innovative curriculum developed by school district personnel. Veteran police officers with several years of street experience, the DARE instructors have a credibility unmatched by regular classroom teachers. Through the DARE lessons, students learn that: real friends will not push them into trying drugs and alcohol; the majority of their peers do not use these substances; being grown up means making their own decisions and coping with problems in a positive way; and they can assert themselves in the face of peer pressure. The DARE curriculum is organized into 17 classroom sessions in which a wide range of teaching activities are used that are designed to encourage student participation and response. (ABL)
ERIC Note: Reprinted from NIJ Reports.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alcohol Abuse; Assertiveness; Curriculum; Drug Abuse; Elementary Education; Elementary School Students; Junior High School Students; Junior High Schools; Peer Influence; Police; Police School Relationship; Prevention; Reports, Descriptive